Goals of care or goals of life? A qualitative study of clinicians' and patients' experiences of hospital discharge using Patient-Oriented Discharge Summaries (PODS) - Nayantara Hattangadi; Paul Kurdyak; Rachel Solomon; Sophie Soklaridis (BMC, 2020)
Abstract Background Recognizing the need for improved communication with patients at the point of hospital discharge, a group of clinicians, patients, and designers in Toronto, Canada collaborated to develop a standardized tool known as the Patient-Oriented Discharge Summary (PODS). Although quantitative results suggest PODS helps mitigate gaps in knowledge, a qualitative inquiry from the clinician and patient perspective of psychiatric hospital discharge using PODS has not been widely explored. Our aim was to explore clinicians' and patients' experiences with PODS. Methods We used a qualitative thematic analysis to explore clinicians' (n = 10) and patients' (n = 6) experiences with PODS. We used convenience sampling to identify and invite potential participants at the Center for Addiction and Mental Health in Toronto, Canada to participate in semi-structured interviews between February 2019 and September 2019. Data were analyzed using a thematic analysis approach to develop descriptive themes. Results Emerging themes from the data between clinicians and patients were both different and complementary. Clinicians described PODS using the concept of "goals of care." They relayed their experiences with PODS as a discrete event and emphasized its role in meeting their "goals of care" for discharge planning. Patients provided more of a "goals of life" perspective on recovery. They characterized PODS as only one facet of their recovery journey and not necessarily as a discrete or memorable event. Patients focused on their outcomes post-discharge and situated their experiences with PODS through its relation to their overall recovery. Conclusions PODS was experienced differently by clinicians and patients. Clinicians experienced PODS as helpful in orienting them to the fulfillment of goals of care. Patients did not experience PODS as a particularly memorable intervention. Due to the information advantage that clinicians have about PODS, it is not surprising that clinicians and patients experienced the PODS differently. This study expanded our understanding of hospital discharge from clinicians and patients perspectives, and suggests that there are additional areas that need improvement.